Analisis Peramalan Permintaan Produk Handuk Tipe A pada PT TUV dengan Metode Time Series - Aryadinata, Rafi; Waluyo, Minto (Fakultas Teknik Universitas Tulang Bawang, 2025)
In the era of globalization, industry and trade in Indonesia are experiencing fierce competition. Technological advances require qualified human resources from formal or non-formal educational institutions with supporting facilities. This research focuses mainly on solving the problem of the type A towel production process which often occurs in the accumulation of goods in the Finishing Warehouse using the Moving Average and Single Exponential Smoothing methods. Due to the current changing market demand, the results of data processing carried out using POM-QM software show that the forecasting method with the Single Exponential Smoothing approach has the lowest Mean Absolute Percentage Error (MAPE) value among other methods, which is 32.637%, so this method was chosen in solving problems in the company because the smaller the error the smaller the possibility of bad things that will happen. Keywords: Demand, Moving Average, Single Exponential Smoothing, Technology